THE INFLUENCE OF SERVICE QUALITY, INCREASING CUSTOMER INTIMACY AND BRAND IMAGE ON CUSTOMER LOYALTY THROUGH INTEREST IN SAVING IN BANK SYARIAH INDONESIA CUSTOMERS KCP WIYUNG SURABAYA - Agus Sarwo Edi; Suherniyatin Suherniyatin (WORLDVIEW ( Development economic and sharia studies journal ), 2022)
This research aims to test and analyze the influence of service quality in improving customer intimacy and brand image on customer loyalty through interest in saving among customers of BSI (Bank Syariah Indonesia) KCP Wiyung Surabaya. The unit of analysis in this research is all customers (Bank Syariah Indonesia) BSIKCP Wiyung Surabaya. Sharia Banking Services, Service Quality, and interest in saving shows significant results on customer interest. The customer intimacy variable, brand image, does not have a significant effect on customer loyalty at Bank Syariah Indonesia KCP Wiyung Surabaya.